Binder Effects on the Creaseability of Pigment Coated Paperboard - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2011)
The primary reason to pigment coating on paperboard is to improve the surface appearance and printability of the paperboard. However, printability is not the only property desired in paperboard. Workability is also important because it also affects productivity and efficiency. Creaseability is the most important property that affects workability. Accurate paperboard package dimensions and predictable foldability characteristics are factors affected by creaseability and they will affect product quality. The aim of this study is to investigate the effects of the proportion of binder in pigment coating mixtures on the creaseability of coated paperboards. The stiffness and creasing values of coated paperboard were compared.
Keywords: Paperboard; Coating; Latex; Creasing